A computer-based testing system to evaluate protective relays as a tool in power system protection education - Martins, L. Sousa (2013)
Submitted by João Marques (joao.marques@estsetubal.ips.pt) on 2013-05-28T08:59:02Z No. of bitstreams: 1 Revista_WiILEY_03_2012.pdf: 5520867 bytes, checksum: 9584fc6d602c3ec2b67b5f46fa4186f8 (MD5)